Flat Housing On The Bank Of The Yogyakarta Code River With The Principle Of Co-Housing - Caesaria Widi Nugraheny (Riviera Publishing, 2025)
Settlements on the banks of the Code River in Yogyakarta are facing challenge big consequence urbanization, which causes improvement density population, degradation environment, and limitations land. Condition This influence quality life public local, especially in aspect social, economic, and ecological. Research This aiming For explore potential implementation the principle of co-housing as solution For increase quality housing and environment in the area Code Riverbank. The research method used is approach descriptive qualitative with studies case in the RT 51 RW 13 area of Jogoyudan Village, Yogyakarta. Data collection was carried out through observation field, interview in-depth, study literature, and analysis spatial. Data is analyzed use approach descriptive, SWOT, and analysis content For identify potential as well as challenge implementation of co-housing. Research result show that the principle of co-housing is able give solution effective to problem area, such as efficiency use space, upgrade interaction social through room communal, and implementation friendly design? environment. Support regulation local, such as Yogyakarta City Regional Regulation Number 1 of 2015 and the Regulation Government Regulation No. 13 of 2021, becomes framework important For support sustainability co-housing implementation. Implications study This show that implementation of co-housing in the area bank river can increase quality life public through approach integrative that combines need social, economic, and ecological. Research This give contribution practical for planning settlement sustainable in the region urban with density resident tall.